The Peer Experience for Older People Encouraging Other Older People to Engage in Resistance Training: A Qualitative Study - Watkins, Paige Marie; Burton, Elissa; Hill, Anne-Marie (2019)
Resistance training (RT) can maintain and improve physical and mental health in older adults, but this population has low levels of RT participation. Linking older people participating in RT (i.e. peers) with those who have not may promote and maintain adherence. This qualitative study explored the experience of peers in encouraging RT participation among older adults. Data were collected using focus groups, researcher observations, and semi-structured interviews. Thematic analysis was conducted. Older people (n=8) who engaged in RT prior to recruitment, participated as peers. Each provided peer-support for between 1-4 RT participants for 6-weeks. The peer role was perceived by peers as potentially leading to a relationship which benefitted both parties. Peers reported that helping and supporting others was a positive experience and raised their self-efficacy. Difficulty initiating contact and differing expectations of peers and RT participants were viewed as challenges. Peer-mentoring could help promote RT participation among older adults.